Financial integration, single monetary policy, and bank efficiency in the eurozone - Rajabi, Ehsan (2015)
This study analyzes the cost and profit efficiency of the banking sector in the euro area Member States during the period from 1999 until 2012. The two-stage approach, the generalized method of moment (GMM) regression model is used to regress the efficiency level obtained from the first stage on factors that could influence the efficiency score. Therefore, the efficiency score measures that derived from the DEA estimations are used as the dependent variable and then regressed upon environmental variables, financial integration, and Single Monetary Policy. The result suggests that the cost and profit efficiency of a given bank is found to be on average negatively related to population density, banking activity, loan management activity, and profitability while economic condition, financial deeping rate, and bank network extension have a positive influence on cost and profit efficiency. Then, this study estimates the relationship between cost and profit efficiency scores and financial integration, which we defined as five groups of competition, bank market ownership, financial liberalization, free capital flow, and the euro area control variables. The results of the GMM estimator suggest that concentration ratio, foreign ownership, domestic credit, and market integration are negatively related to bank cost and profit efficiency while that the coefficient of real credit growth and capital flow have a positive relationship to the cost and profit efficiency score at the 1% level for all years of panel data. Furthermore, empirical findings of bank market power, government budget deficit targeting, and public debt targeting are consistent in both cost and profit efficiency models. Finally, this study analyzes the link between bank efficiency and Single Monterey Policy that is defined by credit channel, interest rate channel, and exchange rate channel and price stability variables in panel regression analysis. The result of GMM estimator shows that there is a positive relationship between efficiency score and bank lending and liquidity but capitalization, exchange rate, inflation targeting, long term interest rate targeting were associated with lower cost and profit efficiency scores.